Daten die bleiben: Ein Abschied von Ueli Hostettler - Ruf, Marcel (Über Mauern blicken - 25 Jahre Forschen im Justizvollzug: Festschrift für Ueli Hostettler zum 65. Geburtstag, 2025)
This article reflects on two decades of collegial cooperation between Marcel Ruf, director of the Lenzburg prison, and Ueli Hostettler. The focus is on personal memories, professional exchanges, and a shared interest in historical, research-related, and prison-related topics. With anecdotes and reflections, the text pays tribute to Hostettler's commitment. (machine translation)